Бобришный угор: рассказы / Василий Белов ;[гравюры В. Лукашова] - Белов Василий Иванович (Детская литература, 1988)
Экземпляры: РБ (20190909) / Инвентарный номер: 19251 / Цена: 1.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6